Social Media Overload dan Kepuasan Belajar pada Mahasiswa Pengguna Tiktok: Peran Emotional Fatigue sebagai Mediator - Nurul Akmali; Dedy Surya (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
The rapid growth of social media usage among university students has significantly transformed learning experiences, particularly through the emergence of information overload. One critical issue is social media overload, which may lead to emotional fatigue and subsequently affect students’ academic satisfaction. This study aimed to examine the relationship between social media overload and learning satisfaction among university students who actively use TikTok, as well as to investigate the mediating role of emotional fatigue. A quantitative research design was employed involving 302 participants aged 18–25 years who were active TikTok users. Data were collected using the Digital Media Overuse Scale, the Emotional Exhaustion Scale, and the Study Satisfaction Scale. Mediation analysis was conducted using PROCESS Macro Model 4. The results indicated that social media overload significantly increased emotional fatigue, which in turn had a negative effect on students’ learning satisfaction. Furthermore, emotional fatigue was found to fully mediate the relationship between social media overload and learning satisfaction. This finding suggests that the negative impact of social media overload on learning satisfaction operates entirely through the mechanism of emotional fatigue. These results highlight the importance of managing digital media consumption to prevent emotional exhaustion and maintain academic well-being. The study provides practical implications for educators and institutions in designing interventions that promote healthy social media use and support students’ emotional regulation in digital learning environments.